Cross-linguistic rhythmic patterns in Persian-English bilingual speakers: Implications for speaker recognition - Homa Asadi; Maral Asiaee (زبان پژوهی)
This study investigates rhythmic patterns in Persian-English bilingual speech, focusing on duration-based measures in a sample of late bilingual adult males. Using various rhythmic measures, including consonantal and vocalic duration, we explored cross-linguistic differences, individual consistency, and speaker identification potential. The results revealed significant differences between Persian (L1) and English (L2), particularly in vocalic measures, whereas consonantal measures exhibited greater consistency. Cross-linguistic correlations were stronger for consonantal measures than for vocalic measures, suggesting higher individual consistency in consonant timing. Speaker identification, conducted through linear discriminant analysis, achieved the highest accuracy with consonantal measures, with stronger performance in L1 than in L2. These findings indicate that while bilingual speakers adjust their rhythmic patterns to suit L2 demands, they retain individual characteristics, especially in consonant timing. This research has implications for understanding bilingual speech production and enhancing speaker recognition technology.